Interactive Storytelling as a Strategy for Improving the English Vocabulary of Young Children - Noerdjanah, Noerdjanah; Haritsa, Nurul Fithriati; Sugiono, Sugiono (Poltekkes Kemenkes Surakarta, 2025)
Background: Community service is an integrated program that involves professionals with the community where community empowerment is directly applied from the beginning to the end of the program. This study aims to introduce early childhood to speak English by using story telling. This activity was carried out at TPQ Masjid Baitul Baasyir in Tohudan Village Colomadu Karanganyar. Methods: The activity was held at the TPQ Masjid Baitul Ba'asyir Karanganyar from February to May 2025 and was attended by 15 children and their parents. The implementation is divided into three stages: the preparation stage (story development and creation of supporting materials), the implementation stage (pre-test, introduction of storytelling concepts, storytelling sessions, and post-test), and the evaluation stage (comparison of pre-test and post-test results, as well as observation of children’s participation). Results: The results of the community service evaluation showed an increase in children's English language skills by 3.07, from a pre-test score of 7.13 to a post-test score of 10.2. This improvement included fluency in speaking, vocabulary mastery, and understanding of story structure. Children and parents also showed enthusiasm and active involvement during the storytelling sessions. Conclusion: The storytelling method has been proven to improve the English language skills of young children. This activity is recommended for wider implementation in non-formal educational institutions such as TPQ and PAUD, and developed through modules and thematic stories, as well as the involvement of parents to strengthen the English language learning process from an early age.